Intercropping of Chickpea and Safflower with Wheat at Different Row Ratios under Conserved Soil Moisture - Sonani, V V; Patel, G G; Jakasanjya, M S; Patel, P T (Annals of Arid Zone, 2016)
A field experiment was conQucted during the winter season of 1992-93, 1993-94 and 1994-95 on clayey Typic Chromustert soil under conserved moisture conditions at Regional Research Station, Gujarat Agricultural University, Arnej to identify compatible intercrop and suitable row ratio for wheat-based intercropping system. Nine treatment combinations, involving wheat, chickpea and safflower alone, and wheat + chickpea and wheat + safflower in 1:I, 2: 1 and 3: I row ratio were tested in randomized block design with four replic~tions. The results revealed that yield of main and intercrops was reduced in intercropping system as compared to sole crop system of respective crops. However, the wheat-equivalent yield was remarkably increased in intercropping system Â·involving safflower as an intercrop. The reverse was true in case of intercropping treatments involving chickpea as an intercrop. On an average, wheat + safflower (3:1) secured the highest wheatequivalent yield (1353.05 kg ha-I), gross income (Rs. 10801 ha-I ) and cost: benefit ratio (1 :3.24) among all the treatments under study.